P685 Evaluation of extragenital swabs for simultaneous neisseria gonorrhoeae culture and nucleic acid amplification testing. (14th July 2019) - Soge, Olusegun; Thibault, Christina; Barbee, Lindley; Pascual, Rushlenne; Rollins, Allison; Golden, Matthew
Abstract : Background: Nucleic acid amplification testing (NAAT) has replaced culture as the predominant test for Neisseria gonorrhoeae (GC). However, antimicrobial susceptibility testing requires culture. We assessed whether a single swab specimen could be used for both NAAT and culture testing for GC. Methods: From May to December 2018, we collected paired specimens from patients presenting to the municipal STD clinic in Seattle, WA who met clinical criteria for gonorrhea culture. One specimen was collected using the BBL CultureSwab plus Amies Gel with Charcoal and one was collected using the Aptima collection kit. Approximately half of BBL specimens were collected by clinicians and half were self-collected by patients. BBL specimens were sent to the laboratory at ambient temperature where they were cultured for GC and then processed and tested using Aptima Combo 2. The second swab was placed in an Aptima transport tube and processed according to the manufacturer's instructions (clinical NAAT). We calculated the agreement between Aptima GC test results among clinical and BBL specimens and the sensitivity of BBL NAAT using the clinical NAAT result as the gold standard. Results: We collected 109 paired rectal specimens (53 clinician-collected and 56 patient-collected) and 104 paired pharyngeal specimens (49 clinician-collected and 55 patient-collected). Twenty-nine (27%) rectal specimens and 19 (18%) pharyngeal specimens were culture positive. Among rectal specimens, 44 (40%) clinical NAATs and 33 (30%) BBL NAATs were positive (90% agreement, BBL 75% sensitive). Among pharyngeal specimens, 59 (57%) clinical NAATs and 39 (38%) BBL NAATs were positive (81% agreement, BBL 66% sensitive). None of the BBL specimens tested positive in the absence of a paired positive clinical NAAT. The sensitivity of NAAT of BBL specimens did not vary substantially between clinician and patient collected specimens. Conclusion: Aptima testing of BBL CultureSwab specimens collected in Amies Gel with Charcoal is insensitive for GC. Disclosure: No significant relationships.